2023
DOI: 10.24059/olj.v27i1.3392
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning for First-Generation and Underrepresented Minoritized Students: A Literature Review Using a Model of Student Engagement

Abstract: First-generation and underrepresented minoritized(URM) studentsmay have greater challenges in online learning than other students. Communities of support can help these highly motivated students be more engaged and successful in the remote learning environment. In this scoping literature review, we identified fifteen categories of first-generation and URM student challenges in online learning as found in peer-reviewed research of the last ten years. We placed these challenges within the Student Engagement mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Attrition rates are considerably higher in online courses than in classroom courses (Aragon & Johnson, 2008; Bawa, 2016; Seery et al, 2021). Numerous studies have revealed that first-generation and underrepresented minoritized students face greater challenges in online learning than others (Gardner & Leary, 2023; Reich & Ruipérez-Valiente, 2019). This exacerbates the already lower graduation rates of Black and Hispanic students (National Center for Education Statistics, 2019).…”
Section: Are Online Programs a Form Of Educational Imperialism?mentioning
confidence: 99%
“…Attrition rates are considerably higher in online courses than in classroom courses (Aragon & Johnson, 2008; Bawa, 2016; Seery et al, 2021). Numerous studies have revealed that first-generation and underrepresented minoritized students face greater challenges in online learning than others (Gardner & Leary, 2023; Reich & Ruipérez-Valiente, 2019). This exacerbates the already lower graduation rates of Black and Hispanic students (National Center for Education Statistics, 2019).…”
Section: Are Online Programs a Form Of Educational Imperialism?mentioning
confidence: 99%